Evaluation of Macroeconomic Models for Financial Stability Analysis - Gunnar Bardsen; Kjersti-Gro Lindquist; Dimitrios P. Tsomocos (Norges Bank, 2006)
As financial stability has gained focus in economic policymaking, the demand for analyses of financial stability and the consequences of economic policy has increased. Alternative macroeconomic models are available for policy analyses, and this paper evaluates the usefulness of some models from the perspective of financial stability. Financial stability analyses are complicated by the lack of a clear and consensus definition of 'financial stability', and the paper concludes that operational definitions of this term must be expected to vary across alternative models. Furthermore, since assessment of financial stability in general is based on a wide range of risk factors, one can not expect one single model to satisfactorily capture all the risk factors. Rather, a suite of models is needed. This is in particular true for the evaluation of risk factors originating and developing inside and outside the financial system respectively.
hdl:11250/2498358
Keywords: E1; E4; E5; G1; G2; 330; financial stability; banks; default; macroeconomic models; policy